STRESS FRACTURES IN ATHLETES - A MULTIFACTORIAL APPROACH TO DIAGNOSIS, TREATMENT, AND PREVENTION - Rolski, Wiktor; Purpura, Aleksandra Anna; Przybylska, Zuzanna; Michalska, Paulina; Przystaś, Bartłomiej; Grzechowiak, Magdalena; Podeszwa, Sebastian; Hobot, Mikołaj Piotr; Dobosz, Gabriela Patrycja; Michalski, Paweł (International Journal of Innovative Technologies in Social Science, 2026)
Background: Stress fractures are common overuse injuries in athletes, resulting from repetitive mechanical loading and microdamage accumulation. Their development is multifactorial, involving biomechanical, metabolic, and behavioral factors. Increasing attention is being paid to data-driven training management and digital monitoring tools in injury prevention. Aim: To review current approaches to the diagnosis, treatment, and prevention of stress fractures in athletes, with emphasis on multifactorial risk models and technology-supported workload management. Materials and Methods: A narrative review was conducted using PubMed and Google Scholar databases. Original studies and reviews involving athletes were analyzed, focusing on diagnostic strategies, treatment approaches, and preventive frameworks. Results: Stress fractures predominantly affect the lower extremities, especially the tibia and metatarsal bones. Their pathogenesis reflects an imbalance between mechanical load and bone adaptation, often linked to training errors, low bone mineral density, and hormonal disturbances. MRI is the most sensitive diagnostic modality. Management depends on fracture location and risk classification. Emerging evidence highlights the role of individualized workload monitoring and wearable technologies in reducing injury risk. Conclusions: Stress fractures require an interdisciplinary approach integrating clinical management with technological and behavioral strategies. Data-driven workload monitoring and metabolic optimization may improve prevention and athlete well-being, with potential implications for broader health management and policy in sport systems.